Urethral reconstruction after total penectomy for urethral cancer - de Jesus, CMN; Kawano, Paulo Roberto [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Trindade, JCS; Agostinho, Aparecido Donizeti [UNESP]; Corrêa, Luiz Antonio [UNESP] (Karger, 2004)
A 59-year-old white man developed a ventral ulcer with irregular limits in the middle portion of the penis. The result of the pathologic analysis was compatible with invasive squamous cell urethral carcinoma. A total penectomy was performed. In these cases, the usually recommended urinary diversion is perineal urethrostomy. However, due to the specifications of the case, perineal urethrostomy could not be performed. The literature did not offer any other alternative for patients with this same condition. Therefore, a urethral reconstruction using a groin skin flap had to be performed. Copyright (C) 2004 S. Karger AG, Basel.
Keywords: urethral cancer; urethral stricture; tubular groin skin flap; penile carcinoma, treatment; perineal urethrostomy